Sustainable development and innovations in marine technologies : proceedings of the 19th International Congress of the International Maritime Association of the Mediterranean (IMAM 2022), Istanbul, Turkey, September 26-29, 2022 /: proceedings of the 19th International Congress of the International Maritime Association of the Mediterranean (IMAM 2022), Istanbul, Turkey, September 26-29, 2022. (2022) - Unknown
No abstract available